Fetal exposure to isotretinoin in Saudi Arabia: a multicenter real-world data analysis from 2015 to 2020 - Yasser Albogami; Ohoud Almadani; Sumaya N. Almohareb; Sultan Alshehri; Abdullah Alkhaibari; Mona Anzan; Alaa Alsharif; Abdulaziz Alhossan; Adel Alrwisan (SAGE Publishing, 2024)
Background: Despite its high efficacy in treating severe acne, isotretinoin is associated with serious side effects, including teratogenicity. However, the extent of isotretinoin exposure during pregnancy in Saudi Arabia remains unknown. Objectives: This study aims to quantify the extent of fetal exposure to isotretinoin in Saudi Arabia and to evaluate adherence to risk minimization measures approved by the Saudi Food and Drug Authority. Design: Retrospective cohort study. Methods: This multicenter retrospective study included a cohort of 6233 women of childbearing ages (WCBAs) who had received isotretinoin therapy between 2015 and 2020. Exposure to isotretinoin use was ascertained from patients' electronic health records and was defined as any positive pregnancy test (urine or serum) or any diagnosis or procedure related to pregnancy occurring during the risk period. We defined the risk period starting from isotretinoin initiation until up to 30 days after the last prescription. We quantified the overall incidence proportion of fetal exposure to isotretinoin by dividing the number of pregnancy cases during the risk period by the total study sample of WCBAs. Results: The cohort predominantly included young females (20-29 years), with a mean age of 24 years. Only 5% of the WCBAs used contraceptives, and 10% have a record of pregnancy testing. During the risk period, 34 pregnancies were identified, yielding a cumulative pregnancy incidence of 5.6 per 1000 WCBAs. Pregnancy outcomes for exposed women were about 5% of births had defects, while abortions accounted for 14.3% of pregnancies. Conclusion: Our investigation shows an alarming incidence of fetal exposure to isotretinoin in Saudi Arabia, substantially surpassing global estimates. These results underscore a critical need for enhanced interventions and robust risk minimization strategies tailored to the distinct challenges faced by the Saudi Arabian population.